Multi-omics analysis of pigmentation related to proanthocyanidin biosynthesis in brown cotton (Gossypium hirsutum L.) - Hinchliffe, Doug J.; Naoumkina, Marina; Thyssen, Gregory N.; Nam, Sunghyun; Chang, SeChin; McCarty, Jack C.; Jenkins, Johnie N. (Frontiers in Plant Science, 2024)
Naturally-colored brown cotton (NBC) fiber is an environmentally friendly raw source of fiber for textile applications. The fiber of some NBC cultivars exhibits flame-retardant properties, which can be used in textiles that require flame resistance. Proanthocyanidins or their derivatives are responsible for the brown pigment in NBC; however, how flame retardancy is related to pigmentation in NBC is poorly understood. To gain insight into brown pigment biosynthesis, we conducted comparative transcripts and metabolites profiling analysis of developing cotton fibers between the brown (MC-BL) and white (MC-WL) cotton near-isogenic lines (NILs), genetically different only in the Lc1 locus. In this study, mass spectrometry was used to detect metabolites in BL and WL developing fibers at 8, 12, 16, 20, 24, 36, and 40 days post anthesis (DPA) and mature fibers. Transcripts analysis was performed at two critical fiber developmental points, 8 DPA (fiber elongation) and 20 DPA (secondary cell wall deposition). We found 5836 (ESI MS positive mode) and 4541 (ESI MS negative mode) metabolites significantly different accumulated between BL and WL. Among them, 142 were known non-redundant metabolites, including organic acids, amino acids, and derivatives of the phenylpropanoid pathway. Transcript analysis determined 1691 (8 DPA) and 5073 (20 DPA) differentially expressed genes (DEGs) between BL and WL, with the majority of DEGs down-regulated at 20 DPA. Organic acids of the citric acid cycle were induced, while most of the detected amino acids were reduced in the MC-BL line. Both cis- and trans-stereoisomers of flavan-3-ols were detected in developing MC-WL and MC-BL fibers; however, the gallocatechin and catechin accumulated multiple times higher. Gas chromatography-mass spectrometry (GC-MS) analysis of fatty acids determined that palmitic acid long-chain alcohols were the main constituents of waxes of mature fibers. Energy-dispersive X-ray spectrometry (EDS) analysis of mature fibers revealed that potassium accumulated three times greater in MC-BL than in MC-WL mature fibers. This study provides novel insights into the biosynthesis of pigments and its association with flame retardancy in NBC fibers.